1999
DOI: 10.1002/(sici)1521-4125(199912)22:12<1017::aid-ceat1017>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hydrodynamic Cavitation

Abstract: A simplified and unified model has been proposed to study the cavitation phenomena in hydraulic devices, with emphasis on the venturi tube and high-speed homogenizer. A turbulence model analogous to the acoustic cavitation has been developed and the dynamics of the cavities as a cluster has been considered. The prediction of the cavitation inception number has been made for various operating conditions and has been compared with the experimental observations. The effect of operating parameters, such as inlet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(52 citation statements)
references
References 14 publications
2
49
0
1
Order By: Relevance
“…The effective cell disruption mechanisms are hydrodynamic cavitation, generated by stirring at high rpm, and shear forces at the solid-liquid interphase. When the impeller tip speed reaches a critical value (8500 rpm), hydrodynamic cavitation occurs due to a local pressure decreases nearly down to the vapor pressure of the liquid (Shirgaonkar et al, 1998;Kumar and Pandit, 1999). Subsequently, as the liquid moves away from the impeller, the liquid pressure restores proportional to the decrease in velocity and the distance from impeller tip and causes the collapse of the cavities (Gogate, 2011).…”
Section: High Speed Homogenizationmentioning
confidence: 99%
“…The effective cell disruption mechanisms are hydrodynamic cavitation, generated by stirring at high rpm, and shear forces at the solid-liquid interphase. When the impeller tip speed reaches a critical value (8500 rpm), hydrodynamic cavitation occurs due to a local pressure decreases nearly down to the vapor pressure of the liquid (Shirgaonkar et al, 1998;Kumar and Pandit, 1999). Subsequently, as the liquid moves away from the impeller, the liquid pressure restores proportional to the decrease in velocity and the distance from impeller tip and causes the collapse of the cavities (Gogate, 2011).…”
Section: High Speed Homogenizationmentioning
confidence: 99%
“…However, this result should be supported by experiments. From the studies of Naidu et al (1994), Shirgaonkar et al (1998) and Kumar and Pandit (1999), it can be concluded that any iodine liberated from the aqueous KI solution would directly indicate the phenomenon of cavitation. The amount of iodine liberated during uid ow in the STANSTED homogenising valve, which is directly proportional to the absorbance value measured (DO), is shown in Fig.…”
Section: Cavitationmentioning
confidence: 99%
“…This causes the cavities that have travelled with the bulk liquid to collapse. Again, similar to the high-pressure homogenizer, there exists a critical rotational speed for the inception of cavitation (Kumar and Pandit 1999;Shirgaonkar et al 1998). …”
Section: High-speed Homogenizermentioning
confidence: 99%
“…3. The constriction can be a venturi (Kumar and Pandit 1999), a single hole orifice (Yan et al 1988) or multiple holes on an orifice plate . Multiple hole orifice plates having different combinations of number, diameter and shape of holes can be constructed (Fig.…”
Section: Low-pressure Hydrodynamic Cavitation Reactormentioning
confidence: 99%